Analysis of Health and Activity Limitation Index (HALex), its distribution, and its distribution by income in Japan, 1989 and 1998 - Yukiko Asada; Yasushi Ohkusa (Osaka University, Institute of Social and Economic Research (ISER), 2002)
It is a widely shared view in the population health field that the future of the analysis of population health lies in the assessment both of the length of life and health-adjusted quality of life, and the parallel examination of the average health and health distribution within a population. Using a nationally representative sample of the 1989 and 1998 wave of the Japanese Comprehensive Survey of Living Conditions of the People on Health and Welfare (CSLC), this research aims to conduct such assessment of the health of Japanese people: examination of the average health-adjusted quality of life, its distribution, and its distribution by income share. This study departs from previous health inequality analyses in the following two ways: (1) construction of a health state measure in the CSLC equivalent to the Health and Activity Limitation Index (HALex) and its application to health inequality analysis, and (2) inclusion of the dead in health inequality analysis. This study found that between 1989 and 1998 overall in Japan the HALex on average slightly reduced (0.005 reduction), its inequality by income slightly reduced (0.002 reduction in the difference between the top 20% and bottom 20% income share groups), and its inequality measured by the Gini Coefficient slightly increased (0.002 increase). Women's HALex was almost always lower than men's, except in earlier ages younger than ten years old. The HALex was more unequally distributed among women than men and in older ages. This analysis shows that the success in the improvement in the length of life in Japan did not always coincide with the improvement in the health-adjusted quality of life and provides a basis for the future population health research.
Keywords: 330; Gesundheitsstatistik; Index; Sterblichkeit; Einkommensverteilung; Gini-Koeffizient; Theorie; Japan; Indexberechnung